Upaya promotif peningkatan pengetahuan tentang imunisasi lanjutan measles rubella dengan aplikasi ponsel AIMMER - Nur Djanah; Yuliantisari Retnaningsih (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
Advanced immunization of Measles Rubella (MR) is an effective strategy to achieve high immunization coverage that will form herd immunity and break the chain of transmission of Measles and Rubella disease. Utilization of the development of android smartphone technology is very possible to develop a system that replaces the role of an expert in the field of health. The purpose is to increase the knowledge of cadres and mothers about the concept of advanced immunization MR through the Android-based application "AIMMER". Activities were held on Sunday, September 5, 2021 in Kembangsari Srimartani Piyungan Bantul. The executors of the activity were 2 lecturers and 3 students of the Department of Midwifery Poltekkes Kemenkes Yogyakarta with the help of 4 field facilitators. The target was cadres and mothers who numbered 40 participants. Activities are carried out according to health protocols, in 1 session a maximum of 10 people by maintaining distance and using masks. The method used is AIMMER android-based application simulation and reflection. The stages of carrying out activities are to explain about the application, goals and benefits, assist the application download process and explain the use of immunization applications, then the target of getting information about MR immunisation through the android-based application "AIMMER". Evaluate by assessing pre-test and post-test on advanced immunization MR knowledge. The post-test was conducted after participants got information about MR immunisation with the app. The results of the activity showed an average pre-test score of 61 and a post-test average value of 76. The conclusion occurred an increase in the level of knowledge of cadres and mothers about  advanced immunization MR after being given a simulation of the android-based application "AIMMER".